Incorporación del riesgo en modelos econométricos de oferta (1990)
high correlation was found between simple risk measures like moving range and moving standard desviation, with the complex measures like naive expectations, adaptive expectations and expectations based on Almon's lags for cotton in Colombia. Although the coefficients of the risk variables presented the correct signs for the area and production models, they were not statistically significant. Apparently, there is no gain from using complex risk measures compared to the simple measures. it is recommended to work on other measures of risk, in order to establish comparisions of the signs and the statistically significance of the coefficients with the results presented in this study.